UJI TOKSISITAS KITOSAN SISIK IKAN HARUAN (Channa striata) TERHADAP SEL VERO - Azwar Fida Maulana; Deby Kania Tri Putri; Aulia Azizah (Dentin, 2022)
ABSTRACTBackground: Periodontal disease is one of the oral disease problems that still need attention. These diseases are among the diseases with the second highest number of sufferers after caries. Periodontitis is a multifactorial that causes inflammation of the periodontal tissue. Periodontitis is caused by bacteria that trigger infectious diseases in the supporting tissues of the teeth. Haruan fish scale chitosan has potential as an antimicrobial, because it contains lysozyme enzymes and aminopolysacharida groups that can inhibit microbial growth. Haruan fish scale chitosan in suppressing bacterial growth is due to its positively charged polycation. Objective: To analyze whether haruan fish scale chitosan is toxic at concentrations of 20%, 40%, 75% and 100% against vero cells. Methods: This study used a true experimental type with a post-test-only design with a control group design to test the toxicity of chitosan do vero cell with concentrations 20%, 40%, 75% and 100% using MTT assay method. The study used 4 treatment groups and 2 control groups with 4 repetitions. Data analyzed with probit analyisis. Results: The largest cell viability values were concentrations of 100% and 75% of 100%, 40% of 81.4% and 20% concentration of 68.1%. Chitosan with concentrations of 20%, 40%, 75% and 100% was said to be non-toxic due to cell viability 60%. Value IC50 93103,354 μg/mL > 1000 μg/mL categorized non-toxic. Conclusion: Haruan fish scale chitosan with concentrations of 20%, 40%, 75% and 100% against vero was tested to vero cells was not have toxic effect. Keywords: Chitosan, Toxicity, Vero cells. ABSTRAKLatar Belakang: Penyakit periodontal termasuk penyakit dengan penderita tertinggi kedua setelah karies. Periodontitis merupakan penyakit peradangan jaringan periodontal. Periodontitis disebabkan oleh bakteri pemicu infeksi pada jaringan penyangga gigi. Kitosan sisik ikan haruan memilki potensi sebagai antimikroba, karena mengandung enzim lysosim dan gugus aminopolysacharida yang dapat menghambat pertumbuhan mikroba. Kitosan sisik ikan haruan menekan pertumbuhan bakteri karena memiliki polikation bermuatan positif. Tujuan: Menganalisis apakah kitosan sisik ikan haruan bersifat toksik pada konsentrasi 20%, 40%, 75% dan 100% terhadap sel vero. Metode: Penelitian ini menggunakan jenis true experimental dengan rancangan post test-only with control group design untuk menguji toksisitas kitosan sisik ikan haruan terhadap sel vero demam konsentrasi 20%, 40%, 75% dan 100% dengan metode MTT assay. Penelitian menggunakan 4 kelompok perlakuan dan 2 kelompok kontrol dengan 4 pengulangan. Data dianalisis menggunakan analisis probit. Hasil: Nilai viabilitas sel terbesar adalah konsentrasi 100% dan 75% sebesar 100%, 40% sebesar 81,4% dan konsentrasi 20% sebesar 68,1%. Kitosan dengan konsentrasi 20%, 40%, 75% dan 100% dikatakan tidak toksik dikarenakan viabilitas sel ≥ 60%. Nilai IC50 93103,354 μg/mL > 1000 μg/mL termasuk kategori tidak toksik. Kesimpulan: Kitosan sisik ikan haruan dengan konsentrasi 20%, 40%, 75% dan 100% yang diujikan terhadap sel vero tidak memiliki sifat toksik.  Kata kunci: Kitosan, Sel Vero, Toksisitas.